2003
DOI: 10.1029/2002jd002973
|View full text |Cite
|
Sign up to set email alerts
|

Determination of reflection coefficients at the top and bottom of elevated strike objects struck by lightning

Abstract: [1] In this paper, we present an analysis of lightning return stroke currents along an elevated strike object. We derive closed form expressions, both in the frequency domain and in the time domain, to calculate the lightning current at any height along a strike object taking into account reflections at the top and at the bottom. The frequency dependence of reflection coefficients is taken into account. We also derive an expression to calculate the reflection coefficient as a function of frequency at the botto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 13 publications
2
27
0
2
Order By: Relevance
“…For the typical RT (5h/c), we can derive the fitted coefficient B for different tall heights from the computed field values as shown below Also, we found that the reflection coefficients of tall objects ranging from observed data presented by Bermudez et al (2003) have not much effect on the far magnetic field, as shown in Fig. 8, and our fitted functions from Eqs.…”
Section: For the Finitely Conducting Groundmentioning
confidence: 94%
See 1 more Smart Citation
“…For the typical RT (5h/c), we can derive the fitted coefficient B for different tall heights from the computed field values as shown below Also, we found that the reflection coefficients of tall objects ranging from observed data presented by Bermudez et al (2003) have not much effect on the far magnetic field, as shown in Fig. 8, and our fitted functions from Eqs.…”
Section: For the Finitely Conducting Groundmentioning
confidence: 94%
“…They are characterized by the same peak value (12 kA), but with different RTs, namely 3h/c and 5h/c. The reflection coefficients are assumed to be constant and equal to ρ t ¼ À0.5 at the top of objects and ρ b ¼ 1 at the bottom of objects, respectively, as shown in Bermudez et al (2003).…”
Section: The Model Introductionmentioning
confidence: 99%
“…On the other hand, Baba and Rakov [7] have pointed out that the characteristic impedance of a vertical cylinder above ground varies with height, which implies that pulses propagating along such a cylinder in general cannot preserve their amplitude and shape. Bermudez et al [21] stated that the controversy regarding the validity of uniform transmission line representation for a vertical conductor above ground "is not settled yet." One of the reasons for the contradictory views found in the literature is the lack of understanding of the mechanism of attenuation of current waves propagating along a perfectly conducting wire.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis was based on engineering models [3][4][5][6][7][8], distributed circuit models [9] and electromagnetic models [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%